A relational structure of voluntary visual-attention abilities - Skogsberg, KatieAnn (J Exp Psychol Hum Percept Perform, 2015)
Many studies have examined attention mechanisms involved in specific behavioral tasks (e.g., search, tracking, distractor inhibition). However, relatively little is known about the relationships among those attention mechanisms. Is there a fundamental attention faculty that makes a person superior or inferior at most types of attention tasks, or do relatively independent processes mediate different attention skills? We focused on individual differences in voluntary visual-attention abilities using a battery of eleven representative tasks. An application of parallel analysis, hierarchical-cluster analysis, and multidimensional scaling to the inter-task correlation matrix revealed four functional clusters, representing spatiotemporal attention, global attention, transient attention, and sustained attention, organized along two dimensions, one contrasting spatiotemporal and global attention and the other contrasting transient and sustained attention. Comparison with the neuroscience literature suggests that the spatiotemporal-global dimension corresponds to the dorsal frontoparietal circuit and the transient-sustained dimension corresponds to the ventral frontoparietal circuit, with distinct sub-regions mediating the separate clusters within each dimension. We also obtained highly specific patterns of gender difference, and of deficits for college students with elevated ADHD traits. These group differences suggest that different mechanisms of voluntary visual attention can be selectively strengthened or weakened based on genetic, experiential, and/or pathological factors.